PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN LKPD UNTUK MENINGKATKAN AKTIFITAS DAN HASIL BELAJAR BIOLOGI SISWA SMP NEGERI 3 SIDUAORI - Hulu, Niat (Universitas Nias Raya, 2023)
This research aims to determine student activities and biology learning outcomes for class VIII-A MIPA students at SMP Negeri 3 Siduaori for the 2022/2023 academic year, which are reviewed based on: (1) Implementation of the learning process, (2) Response, (3) Activities and ( 4) Student learning outcomes in biology learning using the Contextual Teaching and Learning learning model. This type of research uses classroom action research. The subjects of this research were 32 students in class VIII-A. The instruments used were observation sheets on the implementation of the learning process, student response questionnaires, student activity observation sheets, and learning outcomes tests. Data analysis techniques use descriptive and inferential statistics. The research results showed: The results of the research at the first cycle I meeting showed that student learning was classified as good with an average student learning outcome reaching 87% with an incomplete percentage reaching 13% so that the contextual teaching and learning process in cycle I was good. For cycle II, the implementation of contextual teaching and learning averaged 73.57% with a percentage of 90.45% and an incomplete percentage of 9.52% so that the implementation of research in cycle II was declared to have achieved the specified requirements